Ankle Arthroplasty: Patient Reported Outcomes in Preoperative Fixed Equinus. Issue 3 (14th September 2018) - Allport, Jack; Bennett, Adam; Ramaskandhan, Jayasree; Siddique, Malik
Category: Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) has been shown to be an effective treatment for end stage ankle arthritis. Achieving normal anatomical alignment has been shown to be important in long term outcomes and revision rates. Recent data from the British NJR has shown that revision rates are higher in patients with pre-operative fixed equinus. Although there is literature about surgical techniques to deal with pre-operative equinus we are not aware of any papers presenting patient outcomes. We present patient reported outcomes for our cohort of patients with pre-operative fixed equinus compared to those able to achieve a plantigrade ankle. Methods: This is a single surgeon, retrospective cohort study of consecutive cases. A mobile bearing prosthesis was used (Mobility TAA system, DePuy, Raynham, Massachusetts, USA). Cases were identified from a locally held joint registry which routinely records PROMS data pre-operatively and at annual intervals post-operatively. Patients undergoing primary TAA between March 2006 and June 2014 were included, revision procedures along with those with inadequate PROMS data were excluded. PROMS scores used were FAOS (WOMAC Pain, Function and Stiffness), SF-36 scores and patient satisfaction. All pre-operative lateral weight bearing xrays were reviewed to screen for potential fixed equinus deformity (tibia-sole angle >90 degrees). Clinical records were then reviewed to confirm clinical diagnosis of fixed equinus deformity. Results: 259 cases were identified, 95 cases were excluded based on our criteria leaving 164 cases for analysis (mean follow up 61.6 months). 144 were classified as neutral and 20 as fixed equinus. The fixed equinus group were significantly younger (neutral 64.2 vs equinus 53.9, p=0.0002), there was no difference in BMI or length of follow up. There was no difference in baseline scores except WOMAC stiffness, with the fixed equinus group significantly worse (36.9 vs 25.6, p=0.0014). Final PROMS score, change from baseline and patient satisfaction was the same in all domains for both groups. There was no difference in revision rates. Conclusion: A pre-operative fixed equinus deformity does not negatively impact on clinical outcomes in patients undergoing TAA. We are not aware of any previous studies to compare results. As expected the equinus group showed higher levels of stiffness pre-operatively. Contrary to the British NJR dataset we did not find a difference in revision rates.